Identifikasi Potensi Wisata Kuliner Kota Batam - Indra, Febryola; Juliana, Juliana; Hubner, Ira; Sitorus, Nova Irene Bernedeta; Sianipar, Rosianna; Valensky, Sherla (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Traditional culinary delights are the main attraction in the culinary tourism trend. This research identifies the potential for culinary tourism in Batam City using qualitative methods, where the data presented is in the form of words, descriptions and descriptions. This research aims to identify the potential for culinary tourism and gastronomic tourism in Batam, as well as developing the potential for gastronomic tourism in the city. The approach used is descriptive qualitative with the research location in Batam, which was chosen because this city has a variety of culinary tourism potential. Primary data sources were obtained through field observations and in-depth interviews with several key informants who are experts in the culinary field of Batam City. Secondary data was obtained from online documents, literature and scientific journals. Data collection was carried out through direct observation of culinary-related tourism activities. The analysis found a variety of unique culinary delights in Batam City, such as Tarempa Noodles, Gonggong, Malay Laksa, seafood, fish soup, and Bingka Bakar, which have great potential as culinary attractions. As a result, the development of gastronomic tourism in Batam City can take advantage of this culinary wealth to increase the destination's attractiveness and competitiveness.